Pengenalan Lingkungan Sebagai Wujud Informasi Kepada Masyarakat Di Kelurahan Pematang Gubernur - Agung Wijaya; Ilham Aidil Saputra; Jezi Mariani; Nuri Yantari; Prezi Tiananda; Suswati Nasution; Neri Susanti; Tita Septi Handayani (Jurnal Karya Nyata Pengabdian, 2026)
Environmental awareness is a fundamental element in community-based regional development because it plays a role in shaping spatial identity, improving social order, and facilitating accessibility to an area. The community service activities carried out by KKN-T Group 25 aim to increase environmental awareness and identity in RT 33 RW 04, Pematang Gubernur Village, Bengkulu City through the creation of welcome signs. The method used is a participatory approach that directly involves the community from the planning stage to the installation of the sign, as suggested by community empowerment theory. The results of the activity show that the welcome signboard has increased residents' awareness of their neighborhood's identity and made it easier for visitors to recognize the RT 33 area. In addition, the active participation of the community in this activity has strengthened their sense of ownership and social responsibility towards the environment. Thus, the welcome signboard not only functions as a physical marker but also as a social medium that strengthens local community cohesion.